The Influence of the Work Environment on Employee Loyalty - Fauzobihi, Fauzobihi; Riyanto, Andri; Ismuni, Mutdi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The environment and employee loyalty are a unit in the family of human resources science which certainly affects employee performance. This research uses quantitative research. The results of the study are, it can be seen that the results of testing the work environment hypothesis have a significance level of 0.000 and a calculated t value of 5.351 > t table 1.66757. So it can be concluded that Ha is accepted, so it can be said that compensation (X) has a positive and significant effect on employee loyalty because the level of significance of the compensation variable is < 0.05 (0.000 < 0.05) and the calculated t value is > t table ( 5.351 > 1.66757) In this research, employee work loyalty suggests that loyalty is one of the elements used in employee assessment which includes loyalty to their work, position and organization. This loyalty is reflected by the employee's willingness to protect and defend the organization inside and outside of work from being undermined by irresponsible people.